Feeling the Past: Display and the Art of Memory in Latin America - Giunta, Andrea Graciela (2014)
Memory is a compelling and recurring topic in contemporary art. This article examines the mechanisms through which Latin American exhibitions and artists’ urban interventions have addressed the violent and traumatic pasts suffered under decades of dictatorships. The representations of these brutal pasts are activated through images and museographic devices that involve not only the architecture of museums and other sites of memory, but also the choreography and experience of the visitor. I argue that even such formal and abstract structures bear an underlying purpose and politics, which is to produce an emotional contact with the past. By analyzing display sites and artworks dealing with trauma, this article problematizes the relationship between space, memory and history.